Effect of Workload After ACL Reconstruction on Rerupture Rates in NBA Players. Issue 11 (20th November 2020) - Khalil, Lafi S.; Matar, Robert N.; Rahman, Tahsin; Franovic, Sreten; Abbas, Muhammad J.; Hessburg, Luke; Mehran, Nima; Okoroha, Kelechi R.
Background: Rupture of the anterior cruciate ligament (ACL) is a common and potentially career-altering injury sustained by players in the National Basketball Association (NBA). Strategies have been employed by the league to prevent reinjury of players after ACL reconstruction (ACLR), including minute restrictions and rest games; however, it remains unknown whether workload metrics after ACLR influence the risk for reinjury and revision surgery. Purpose: To evaluate whether workload changes after return to play (RTP) from primary ACLR influences the risk of rerupture in NBA players. Study Design: Case-control study; Level of evidence, 3. Methods: We identified NBA players from 1975 to 2018 who underwent primary ACLR as well as those who required revision ACLR. Primary outcomes included workload measures such as games played, games started, and minutes per game. Secondary outcomes included in-game performance statistics. Statistical analysis was used to compare relative workload and performance 3 years before and 3 years after undergoing primary ACLR. Workload was also compared between the control group of NBA players who underwent primary ACLR and those who required revision ACLR. Results: A total of 68 players who underwent primary ACLR were included, 8 of whom subsequently required revision ACLR. In their first season upon RTP, control players (primary ACLR) demonstrated a significant reduction in all workload metrics relative to the season before injury ( P < .001), while the revision group demonstrated an unchanged to increased workload. In a comparison between the primary and revision groups during the first season after RTP, the primary group demonstrated significantly fewer games started (mean ± SD, 22.2 ± 3.0 vs 35.8 ± 8.3; P = .039) and minutes per game (20.5 ± 1.1 vs 27.0 ± 3.1; P = .048) than revision players. The primary ACLR group demonstrated reduced cumulative workload trends for the first 3 years after RTP relative to 3 years before injury, which was not demonstrated in the revision ACLR group, albeit statistically insignificant. Conclusion: Our study found that after ACLR, a reduction in workload parameters relative to preinjury baseline was associated with players who did not sustain rerupture. Further study is required to determine if workload measures following RTP from primary ACLR should be individualized relative to preinjury baseline.